MicroRNA-34a in Colorectal Cancer: Linking Epigenetic Regulation to Tumor Suppression - Saja Ali Abbas (Wasit Journal for Pure Sciences)
:        Colorectal cancer (CRC) persists as a lethal malignancy and ranks as the third foremost cause of cancer-related mortality. The study aimed to expression levels of the miRNA-34a gene were performed and aby the qRT-PCR SYBR Green test to estimate the expression of the target gene and determine levels of Hb, PLT, WBC, and RBC in CRC patient and control.  In present study blood samples collected from 60 subjects (20 control and 40 patient with CRC), (females and  males) with different aged. The collection of samples and the practical work for this study from January 2023 to November 2023, Concerning The mean value of CBC parameters, the analysis showed that there was statistical difference in Hb (11.84 ± 2.21) and PLT (297.26 ± 127.06) biomarkers in the patient group with P value ≤ 0.05. However, the WBC and RBC showed no significant difference in patient with CRC compared to control group with mean value (7.52 ± 2.69, 4.54 ± 0.71) respectively. Endogenous control gene U6 miRNA levels were amplified and utilized to normalize the miRNA-34a gene levels. U6 showed no-significant variation between patient and control samples accordingly used as house keeping gene for miRNA34-a Which did not show any noticeable change between patient and control group in blood sample. Can conclude from that miRNA34-a could not use as marker for CRC in blood and might be used as biomarker in tissue because it more specific to the regulation role for miRNAs.